2015
DOI: 10.1128/jvi.01524-15
|View full text |Cite
|
Sign up to set email alerts
|

Bub1 in Complex with LANA Recruits PCNA To Regulate Kaposi's Sarcoma-Associated Herpesvirus Latent Replication and DNA Translesion Synthesis

Abstract: Latent DNA replication of Kaposi's sarcoma-associated herpesvirus (KSHV) initiates at the terminal repeat (TR) element and requires trans-acting elements, both viral and cellular, such as ORCs, MCMs, and latency-associated nuclear antigen (LANA). However, how cellular proteins are recruited to the viral genome is not very clear. Here, we demonstrated that the host cellular protein, Bub1, is involved in KSHV latent DNA replication. We show that Bub1 constitutively interacts with proliferating cell nuclear antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…A recent study showed that siRNA mediated depletion of RFC ATPase compromised the interaction between RFC and LANA and directly affected LANA-mediated replication and episome maintenance (Moldovan et al, 2007 ). Similarly, it has been shown that cellular mitotic checkpoint kinase, Bub1 plays a significant role in LANA mediated recruitment of PCNA to the TR to initiate viral replication in S phase (Sun et al, 2015 ). Bub1 establishes a molecular complex with PCNA and LANA and was found to be critical to promote LANA mediated mono-ubiquitination of PCNA (Sun et al, 2015 ).…”
Section: Mechanism Of Kshv Latent Dna Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that siRNA mediated depletion of RFC ATPase compromised the interaction between RFC and LANA and directly affected LANA-mediated replication and episome maintenance (Moldovan et al, 2007 ). Similarly, it has been shown that cellular mitotic checkpoint kinase, Bub1 plays a significant role in LANA mediated recruitment of PCNA to the TR to initiate viral replication in S phase (Sun et al, 2015 ). Bub1 establishes a molecular complex with PCNA and LANA and was found to be critical to promote LANA mediated mono-ubiquitination of PCNA (Sun et al, 2015 ).…”
Section: Mechanism Of Kshv Latent Dna Replicationmentioning
confidence: 99%
“…Similarly, it has been shown that cellular mitotic checkpoint kinase, Bub1 plays a significant role in LANA mediated recruitment of PCNA to the TR to initiate viral replication in S phase (Sun et al, 2015 ). Bub1 establishes a molecular complex with PCNA and LANA and was found to be critical to promote LANA mediated mono-ubiquitination of PCNA (Sun et al, 2015 ). Two more cellular proteins shown to be critical for KSHV genome replication and maintenance are the components of Timeless-dependent DNA replication fork protection complex, Tim and Tipin (Dheekollu et al, 2013 ).…”
Section: Mechanism Of Kshv Latent Dna Replicationmentioning
confidence: 99%
“…Immunoprecipitation (IP) and Western blotting were performed as described previously [ 70 ]. Briefly, cells were collected and were lysed in lysis buffer (10 mM Tris, 1% NP-40, 2 mM EDTA, 150 mM NaCl [pH 7.5]) with protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence assays (IFA) were performed as previously described (39). Briefly, the cells were fixed with 4% paraformaldehyde and 0.1% Triton X-100 for 15 to 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…pCDNA3-RTA, PGEX-RTA, His-Uba1, HisUbc5a, and His-ubiquitin were described previously (39,40). The coding sequences (CDS) of MHC-II molecules were generated by using PCR and cloned into pA3M vector using the following primers: for HLA-DR␣, 5=-AT AAGAATGCGGCCGCCAGAGGCCCCCTGCGTTCTG-3= and 5=-CG GGATCCATGGCCATAAGTGGAGTCCC-3=; for HLA-DR␤, 5=-CGGGA TCCATGGTGTGTCTGAAGTTCCC-3= and 5=-ATAAGAATGCGGCC GCGCTCAGGAATCCTGTTGGCT-3=; for HLA-DP␣, 5=-CGGGATCC ATGCGCCCTGAAGACAGAAT-3= and 5=-ATAAGAATGCGGCCGCC AGGGTCCCCTGGGCCCGGG-3=; for HLA-DP␤, 5=-CGGGATCCATG ATGGTTCTGCAGGTTTC-3= and 5=-ATAAGAATGCGGCCGCTGCA GATCCTCGTTGAACTT-3=; for HLA-DQ␣, 5=-CGGGATCCATGATC ACATTCCTGCCGCT-3= and 5=-ATAAGAATCGGCCGCCAATGGCC CTTGGTGTCTGG-3=; for HLA-DQ␤, 5=-CCCAAGCTTATGTCTTGG AAGAAGGCTTT-3= and 5=-ATAAGAATGCGGCCGCGTGCAGAAGC CCTTTCTGAC-3=.…”
Section: Methodsmentioning
confidence: 99%